Waloryzacja turystyczna obszarów wiejskich województwa wielkopolskiego - Przezbórska, Lucyna (Tourism Valorization of Rural Areas of the Wielkopolska Region, 2006)
Rural areas create the environment for development of rural tourism and agritourism, facilitating or making it difficult. There is a necessity to characterize the areas, including characteristics determining the number and structure of agritourism and rural tourism enterprises. The Wielkopolska region and especially some of the areas seem to be potentially favourable for agritourism and rural tourism development. The main purpose of the paper is to valorize rural agritourism areas of the Wielkopolska region. Hellwig methodology (1968) is used to construct aggregate measure for tourism valorization of rural areas. On the basis of the calculated values of the aggregate index areas advantaged and disadvantaged for rural tourism and agritourism development in the Wielkopolska region are pointed out.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 254-260